2016
DOI: 10.1615/critrevimmunol.2016017507
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Effects of Melphalan and Usefulness in Adoptive Cell Therapy with Antitumor CD4+ T Cells

Abstract: The alkylating agent melphalan is used in the treatment of hematological malignancies, especially multiple myeloma. In the past, the usefulness of melphalan has been solely attributed to its cytotoxicity on fast-growing cancerous cells. Although the immunomodulatory effects of melphalan were suggested many years ago, only recently has this aspect of melphalan’s activity begun to be elucidated at the molecular level. Emerging evidence indicates that melphalan can foster an immunogenic microenvironment by induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 126 publications
(129 reference statements)
0
18
0
Order By: Relevance
“…At the end of the experiment, concerning prodrugs administrations, the normalized cell index of free MPH treated cells was~245-fold lower in healthy cells, describing a very low selectivity toward cancer versus healthy cells as described by several studies, and the frequent side-effects of free MPH (Kühne et al, 2009;Kuczma et al, 2016). Remarkably, from analysis of the normalized cell index ratio between mPEG-TK-MPH and free MPH in both types of cells ( Figures 3A, B), we can conclude that mPEG-TK-MPH was significantly favorable in terms of safety treated in healthy cells with minimal toxicity and showed good selectivity in the case of cancer cells, with normalized cell index ratios at 48 h treatment of (295 vs 1.8, respectively).…”
Section: Cytotoxicity Studies Of Mpeg-tk-mph and Mpeg-mph On Murine Gmentioning
confidence: 77%
See 2 more Smart Citations
“…At the end of the experiment, concerning prodrugs administrations, the normalized cell index of free MPH treated cells was~245-fold lower in healthy cells, describing a very low selectivity toward cancer versus healthy cells as described by several studies, and the frequent side-effects of free MPH (Kühne et al, 2009;Kuczma et al, 2016). Remarkably, from analysis of the normalized cell index ratio between mPEG-TK-MPH and free MPH in both types of cells ( Figures 3A, B), we can conclude that mPEG-TK-MPH was significantly favorable in terms of safety treated in healthy cells with minimal toxicity and showed good selectivity in the case of cancer cells, with normalized cell index ratios at 48 h treatment of (295 vs 1.8, respectively).…”
Section: Cytotoxicity Studies Of Mpeg-tk-mph and Mpeg-mph On Murine Gmentioning
confidence: 77%
“…This may be due to a higher cell uptake favored by L-type amino acid transporters (LATs) (Kühne et al, 2009) (as L-type amino acid transporter 1, LAT1), which transport neutral amino acids, including leucine. This transporter is present also in glioma cells, including C6 (Lin et al, 2004;Nawashiro et al, 2005;Nawashiro et al, 2006;Kuczma et al, 2016), and can promote MPH active transport into cells (Lin et al, 2004). In addition, taking into consideration its hydrophobic nature, passive transport of the free form of the drug cannot be excluded (Kühne et al, 2009).…”
Section: Cytotoxicity Studies Of Mpeg-tk-mph and Mpeg-mph On Murine Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the literature data between the treatments of the patients included in our study and their relationship with p450 seems important in terms of explaining the significant differences we obtained in terms of OS and PFS. It is necessary to mention the publications on the relationship between bortezomib, cyclophosphamide, dexamethasone, lenalidomide, and the p450 enzyme system and melphalan used in ASCT [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Melphalan is eliminated by both renal excretion and spontaneous chemical degradation to its mono-and di-hydroxy metabolites. Therefore, no relationship has been described between the p450 system and melphalan activity [21,22]. Studies on lenalidomide have also shown that it has no effect on any of p450 cytochrome enzymes [23].…”
Section: Discussionmentioning
confidence: 99%